Social deprivation and exclusion in Parkinson’s disease: a cross-sectional and longitudinal study - Aline Schönenberg; Tino Prell; Konstantin G Heimrich (BMJ Open)
Objective To describe prevalence and associated factors of social deprivation in people with Parkinson’s disease (PwPD).Design Cross-sectional and longitudinal cohort study.Setting Data were taken from the Survey of Health, Ageing and Retirement in Europe (SHARE), a multidisciplinary, cross-national and longitudinal research project.Participants Community-dwelling adults from waves 5 (2013, n=66 188) and 6 (2015, n=68 186) of the SHARE dataset. After longitudinal analyses, participants in wave 5 can be retrospectively divided into the following three subgroups: PwPD at wave 5 (n=559), people newly reported PD from wave 5 to wave 6 (prodromal PD; n=215) and people without PD (n=46 737).Outcome measures The prevalence and associated factors of social deprivation in PD, its impact on quality of life (QoL) and its onset within the course of PD.Results PwPD had higher indices for material and social deprivation than non-PD participants, and 20% of PwPD were at risk of social exclusion. Social deprivation alone accounted for 35% and material deprivation for 21% of QoL variance and remained significant predictors of QoL after adjustment for cofactors. Social deprivation and risk of social exclusion were already increased in people with prodromal PD, and accordingly preceded PD diagnosis in wave 6.Conclusions For the treatment of PD, we should consider the impact of social deprivation and exclusion on QoL and their association with mental and physical functioning. However, the relevance of social deprivation as a prodromal phenomenon requires further investigation.